Molecular characterization of sheep major histocompatibility complex (OVAR-MHC) Class II DQA1 gene in two Egyptian breeds - Amr M. A. Mohamed (South Valley University, 2021)
The major histocompatibility complex (MHC) is a large locus on vertebrate DNA that contains a set of closely related polymorphic genes coding for cell surface proteins essential for an adaptive immune system. MHC is thought to be under strong selection pressure because of its main role in infectious disease resistance. Thus, the pattern of different MHC genes variation should reflect this selection pressure in animal's natural populations. To test this hypothesis, we investigate the nature and frequency of polymorphism of the sheep MHC class II DQA1 gene in two different common local Egyptian sheep breeds (Ossimi and Saidi). Ovar-DQA1 gene is considered one of the most important response genes in the MHC region. In the current study, blood samples of 50 Egyptian sheep from two breeds (32 Ossimi and 18 Saidi) with different ages and sex and from seven different farms in Qena governorate were collected for DNA extraction and PCR amplification. The PCR products of 18 DQA1 alleles were examined using direct sequencing, for the detection of polymorphism in a functionally relevant domain of the DQA1 gene. Among the investigated samples the phylogenetic tree reconstruction and sequence comparison revealed different DQA1 alleles. Thirty-two sheep samples lacking DQA1, five different alleles were identified for the two breeds. The multiple sequence alignment illustrates nucleotide polymorphism and conserved regions in the identified sequences. This variation leads to a better understanding of the genetic makeup of Ovar-MHC and facilitates the selective breeding programs to determine the resistance and susceptibility to disease in sheep.